An antibiotic stewardship initiative focused on community-acquired bacterial pneumonia (CABP) in outpatient clinics and urgent care centers: a 2023–2024 community health system experience - Tomefa E. Asempa; Tyler Ackley; Kristin E. Linder; Cara D. Riddle; Eric Walsh; David P. Nicolau (Antimicrobial Stewardship & Healthcare Epidemiology)
Abstract